Nilai Filosofis Tri Pitama dalam Arsitektur Bali - I Nyoman Subrata (Sanjiwani: Jurnal Filsafat, 2020)
This article describes the philosophical values ​​contained in a building structure that has Tri Pitama elements, namely the three main pillars informing the building concept. The three pillars are adapted to the science of negotiation (Balinese architecture), namely the aspects of tattwa, morals, and events. The three pillars form the head, body, and feet of every Balinese building structure. This concept is philosophically aligned with the aspects of Bhuwana Agung and Bhuwana Alit. The next tendency is to balance it because tri pitama is the embodiment of philosophical concepts related to Tri Hita Karana, Tri Angga, Tat Twam Asi, Tri Loka, Kala Patra Village, Dewata Nawa Sanga, and Rwa Bhineda. These elements form a clearer Balinese architectural development towards the direction and goals in developing the basic concept of the Tri Pitama. Tri Pitama forms buildings under the Tattwa in literature, morals that make up a forming element in the development of Balinese architecture and events that are used as a form of devotion with various means and ceremonies that create harmony with the environment, humans, and God. Through this study, about literature studies and observations of the construction of Balinese architecture. Thus, the philosophical values ​​of Balinese architecture are used as the basis for interpreting and functioning the Tri Pitama concept in Balinese buildings.